The complete chloroplast genome of Viola vaginata (Violaceae), an endemic species of the snowy region in Japan - Yayoi Takahashi; Masato Fujiwara; Masaaki Ozeki; Masayuki U. Saito; Takaya Iwasaki (Mitochondrial DNA. Part B. Resources)
Viola vaginata, a perennial herb in subsection Stolonosae, is endemic to the snowy mountainous regions on the Sea of Japan side of Japan. Its complete chloroplast genome was 156,056 bp in length, comprising one large single-copy region (86,407 bp), one small single-copy region (17,301 bp), and two inverted repeat regions (27,174 bp each). It contained 111 unique genes, including 77 protein-coding genes, 30 transfer RNA genes, and 4 ribosomal RNA genes. Phylogenetic analysis placed V. vaginata in a clade with subsection Biobatae species and some Patellares species, while other Patellares species formed a distinct clade, contrasting with previous nuclear ITS results. These findings highlight the phylogenetic complexity within Viola.